2017
DOI: 10.1016/j.shaw.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Incidence in Asbestos-Exposed Workers: An Update on Four Finnish Cohorts

Abstract: BackgroundWe assessed the cancer risks of four different Finnish asbestos-exposed cohorts. We also explored if the cohorts with varying profiles of asbestos exposure exhibited varying relative risks of cancer.MethodsThe incident cancer cases for the asbestos-exposed worker cohorts were updated to the end of 2012 using the files of the Finnish Cancer Registry. The previously formed cohorts consisted of asbestos mine workers, asbestosis patients, asbestos sprayers, and workers who had taken part in a screening s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 10 publications
1
18
1
1
Order By: Relevance
“…Asbestos textile is primarily pulled by the flow of pulmonary lymph from lung interstitium (primary translocation) to reach the bloodstream, and is continuously distributed to the whole body (secondary translocation). Since the translocation process of asbestos textile continues for decades, the latent period of asbestos-related disease is as long as 10 to 50 years [ 31 , 34 , 38 , 39 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Asbestos textile is primarily pulled by the flow of pulmonary lymph from lung interstitium (primary translocation) to reach the bloodstream, and is continuously distributed to the whole body (secondary translocation). Since the translocation process of asbestos textile continues for decades, the latent period of asbestos-related disease is as long as 10 to 50 years [ 31 , 34 , 38 , 39 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, with the ban of the product in high-income countries in the late 20 th Century this has resulted in marketing of the product to less developed, lower and middle-income countries, considered as having a weak regulatory approach toward the product ban implementation. As reported by Marsili et al (2016) "suspicions that lung cancer may be associated with asbestos exposure were first reported in the USA and the UK in the 1930s, and decades later reports of pleural tumours associated with asbestos exposure followed". Several articles have reported on the association between asbestos fibre exposure to several forms of ill health that include pulmonary fibrosis, chronic obstructive pulmonary disease, pleural plaques, pleural effusion, pulmonary fibrosis (asbestosis), lung cancer, and mesothelioma of the pleura or peritoneum in humans (Harington and McGlashan, 1998, Joshi and Gupta, 2004, Braun and Kisting 2006, Tan and Warren, 2009, Bunderson-Schelvan et al 2011, Lee et al 2013, Hashim and Boffetta, 2014, WHO, 2014, WHO, 2015, Nynäs et al 2016, Kratzke and Kratzke, 2018.…”
Section: Introductionmentioning
confidence: 99%
“…The International Agency for Research on Cancer (IARC) in 1973 categorised asbestos as a human carcinogen and 44 years later, WHO (2014) further confirms the relationship between exposure to either forms of asbestos -chrysotile, amosite and anthrophyllite or their mixture and the increased risk of lung cancer and mesothelioma among workers and those living around asbestos factories and mines, as well as among individuals living with asbestos workers. To date, countless studies into occupational and non-occupational exposure to asbestos have demonstrated strong links to asbestosis, mesothelioma and pulmonary disease and other diseases (Joshi and Gupta, 2004;Braun and Kisting 2006, WHO, 2012, Lee et al 2013, WHO, 2014Marsili et al 2016). In considering the extensive epidemiological evidence of asbestos as a human carcinogen, over 50 countries have so far banned asbestos production and use, while several nations have applied strict restrictions on its use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent pooled mortality analysis of 43 Italian cohorts of workers exposed to asbestos followed up between 1970 and 2010 confirmed increased mortality for pleura and peritoneal mesothelioma and lung cancer [19]. In particular, mortality rates from pleural cancer showed an increasing trend during the first 30 years since first exposure to asbestos, which then reaches a plateau thereafter.. A study of four Finnish asbestos-exposed cohorts followed up between 1967 and 2012 revealed 3 to 100-fold increased incidence for mesothelioma and 2 to 10-fold for lung cancer [20]. The Swedish component of the Nordic Occupational Cancer study (NOCCA) reported increased risk of mesothelioma with a clear dose-response relationship [21].…”
Section: Introductionmentioning
confidence: 99%